Value of bacterial culture of vaginal swabs in diagnosis of vaginal infections - Nenadić, Dane; Pavlović, Miloš (Vojnosanitetski pregled, 2015)
Bacground/Aim. Vaginal and cervical swab culture is still very common procedure in our country’s everyday practice whereas simple and rapid diagnostic methods have been very rarely used. The aim of this study was to show that the employment of simple and rapid diagnostic tools [vaginal fluid wet mount microscopy (VFWMM), vaginal pH and potassium hydroxide (KOH) test] offers better assessment of vaginal environment than standard microbiologic culture commonly used in Serbia. Methods. This prospective study included 505 asymptomatic pregnant women undergoing VFWMM, test with 10% KOH, determination of vaginal pH and standard culture of cervicovaginal swabs. Combining findings from the procedures was used to make diagnoses of bacterial vaginosis (BV) and vaginitis. In addition, the number of polymorphonuclear leukocytes (PMN) was determined in each sample and analyzed along with other findings. Infections with Candida albicans and Trichomonas vaginalis were confirmed or excluded by microscopic examination. Results. In 36 (6%) patients cervicovaginal swab cultures retrieved several aerobes and facultative anaerobes, whereas in 52 (11%) women Candida albicans was isolated. Based on VFWMM findings and clinical criteria 96 (19%) women had BV, 19 (4%) vaginitis, and 72 (14%) candidiasis. Of 115 women with BV and vaginitis, pH 4.5 was found in 5, and of 390 with normal findings 83 (21%) had vaginal pH 4.5. Elevated numbers of PMN were found in 154 (30%) women – in 83 (54%) of them VFWMM was normal. Specificity and sensitivity of KOH test and vaginal pH determination in defining pathological vaginal flora were 95% and 81%, and 79% and 91%, respectively. Conclusion. Cervicovaginal swab culture is expensive but almost non-informative test in clinical practice. The use of simpler and rapid methods as vaginal fluid wet mount microscopy, KOH test and vaginal pH offers better results in diagnosis, and probably in the treatment and prevention of sequels of vaginal infections.